Don't cry over spilled water: identifying risks and solutions for produced water spills - Shores, Amanda Rose, author; Laituri, Melinda, advisor; Butters, Gregory, committee member; Pilon-Smits, Elizabeth, committee member; Gooseff, Michael, committee member (Colorado State University. Libraries, 2017)
Resource requirements and future energy generation requires careful evaluation, particularly due to climate change and water scarcity. This thesis discusses one aspect of energy generation linked to water; oil-and-gas extraction and the large volumes of waste water produced, otherwise known as "produced water". This research focuses on surface spills of produced water, their ramifications, safeguards against groundwater contamination at spill sites and potential remediation strategies. Produced water contains a variety of contaminants that include the group of known toxins, BTEX (benzene, toluene, ethylbenzene and xylene), and high salt concentrations. A combination of factors such as large volumes of generated produced water, the need for storage and transportation across large distances and the toxic-and-mobile nature of produced water constituents creates risks for spills that can pollute groundwater. Spills occur regularly, particularly in Weld County, Colorado, where the demand for natural gas is high. To answer spill-related hypotheses, a multitude of methodology were employed: modeling, greenhouse experimentation, gas chromatography and summarization of spill reports and statistical analyses. Using publicly available spill data, this research found that the frequency of oil-and-gas related spills and the average spilled volume has increased in Weld County from 2011–2015. Additionally, the number of spills that have resulted in groundwater contamination has increased in the area. By focusing on the oil-and-gas operators responsible for these spills, a linear relationship was found between the volumes of oil-and-gas produced compared to the volumes of produced-water generated. However, larger oil-and-gas producers did not show a linear relationship between oil-and-gas produced and produced-water generated, such that larger producers were more efficient and generated less water per unit of energy. So while scale-up efficiency seems to exist for produced-water generation, no mitigation of spill volume would be obtained by utilizing larger producers. Regardless of which operator was responsible for the spill, the groundwater depth at a spill site significantly predicted when a spill would result in groundwater contamination. This result was also validated though modeling; shallow depths to groundwater as well as larger spill volumes and coarse soil textures contributed to higher concentrations of groundwater contamination. Previous research has shown that a large fraction of spills occur at well pads. Our results suggest that fracking-site selection should preclude areas where the groundwater is shallow and soil is coarsely textured. Additionally, precautions should be taken to reduce the volume of spilled produced water to reduce the risk of groundwater contamination. This research additionally sought to reduce contaminant migration in soils towards groundwater at produced-water spill sites. In a greenhouse study it was shown that foxtail barley (Hordeum jubatum) and perennial ryegrass (Lolium perenne), can tolerate high salt concentrations in produced water while taking up minute levels of BTEX. The presence of plants changed the concentration of BTEX and naphthalene in the soil, but the direction of the change depended upon the particular plant and varied across contaminants. Additionally, the roots of either species saw no decrease of biomass upon exposure to BTEX and salt but shoots biomass was significantly reduced for foxtail barley. These results suggest that these grasses would not be capable of addressing large concentrations of BTEX at spill sites; however, these plants would be useful near well pads that regularly experience smaller spills, thus being able to tolerate spills while continually removing small amounts of BTEX in the soil. In conclusion, this thesis sought to identify holistic tools for produced-water spill prevention, mitigation and remediation to lessen environmental and health concerns while creating minimal disturbance to the natural landscape. The results lend themselves to important management information applicable to Weld County, CO but with lessons that others can draw upon elsewhere. This dissertation highlights areas for improved regulation and best management practices that can preemptively reduce the risk for groundwater contamination from produced water spills.
Zip file contains data spreadsheet.